Simul 5 - free dynamic simulator of electrophoresis - Hruška, Vlastimil; Jaroš, Michal; Gaš, Bohuslav (Electrophoresis, 2006)
We introduce the mathematical model of electromigration of electrolytes in free solution together with free software Simul, version 5, designed for simulation of electrophoresis. The mathematical model is based on principles of mass conservation, acid-base equilibria, and electroneutrality. It accounts for any number of multivalent electrolytes or ampholytes and yields a complete picture about dynamics of electromigration and diffusion in the separation channel. Additionally, the model accounts for the influence of ionic strength on ionic mobilities and electrolyte activities. The typical use of Simul is: inspection of system peaks (zones), stacking and preconcentrating analytes, resonance phenomena, and optimization of separation conditions, in either CZE, ITP, or IEF.
Keywords: elektroforéza; Computer Simulation; Software; software; Mathematics; matematika; teoretické modely; Models, Theoretical; počítačová simulace; Electrophoresis